Fabrication of Magnetite/Silica/Titania Core-Shell Nanoparticles - Pang, Suh Cem; Kho, Sze Yun; Chin, Suk Fun (Hindawi Publishing Corporation, 2012)
Fe3O4/SiO2/TiO2 core-shell nanoparticles were synthesized via a sol-gel method with the aid of sonication. Fe3O4 nanoparticles were being encapsulated within discrete silica nanospheres, and a layer of TiO2 shell was then coated directly onto each silica nanosphere. As-synthesized Fe3O4/SiO2/TiO2 core-shell nanoparticles showed enhanced photocatalytic properties as evidenced by the enhanced photodegradation of methylene blue under UV light irradiation.